Angelo Mangiarotti, Posizione dell’architettura (Position de l’architecture), 1952 : un film comme première sédimentation intellectuelle - Yves Ambroset (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Between 1952 and 1953 the Italian architect Angelo Mangiarotti (1921-2012) made the film Posizione dell'architettura. The aim of this study is to analyse this document, placing it in its biographical and historical context. It aims to identify the formal characteristics of the work and its content, at a crucial time for the development of the architect's architectural language. The aim is also to identify what makes this film a work of theory, and to demonstrate how this initial intellectual research will have a decisive influence on the architect's entire output.